Owls - Marsh, Laura; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2014)
In this book, young readers will explore the feathery world of adorable owls. Follow these curious-looking creatures through their wooded habitats, learn how owls raise their young, hunt, and protect themselves. Beautiful photos and carefully leveled text make this book perfect for reading aloud or for independent reading.
Who are you? -- Many owls -- Owls everywhere -- Hotshot hunters -- Dinnertime -- Owl homes -- Hide and seek -- 7 cool owl facts -- A nest of babies -- Who hoots? -- What in the world? -- Picture glossary.
At head of title on cover: National Geographic kids.
Target age: 4-6 years old.
Keywords: Owls -- Juvenile literature; Juvenile nonfiction; Easy reader